Coronary Microcirculation Downstream Non‐Infarct‐Related Arteries in the Subacute Phase of Myocardial Infarction: Implications for Physiology‐Guided Revascularization. Issue 9 (7th May 2019) - Mejía‐Rentería, Hernán; Lee, Joo Myung; van der Hoeven, Nina W.; Gonzalo, Nieves; Jiménez‐Quevedo, Pilar; Nombela‐Franco, Luis; Núñez‐Gil, Iván J.; Salinas, Pablo; Del Trigo, María; Cerrato, Enrico; van Royen, Niels; Knaapen, Paul; et al.
Abstract : Background: Concerns exist about reliability of pressure‐wire‐guided coronary revascularization of non‐infarct‐related arteries (non‐IRA). We investigated whether physiological assessment of non‐IRA during the subacute phase of myocardial infarction might be flawed by microcirculatory dysfunction. Methods and Results: We analyzed non‐IRA that underwent fractional flow reserve, coronary flow reserve, and the index of microcirculatory resistance assessment. Microcirculation and hyperemic response were evaluated in 49 acute myocardial infarction patients (59 non‐IRA) and compared with a matched control group of 46 stable angina (SA) patients (59 vessels). Time between acute myocardial infarction to physiological interrogation was 5.9±2.4 days. Fractional flow reserve was similar in both groups (0.79±0.11 in non‐IRA versus 0.80±0.13 in SA vessels, P =0.527). Lower coronary flow reserve values were found in non‐IRA compared with SA vessels (1.77 [1.25–2.76] versus 2.44 [1.63–4.00], P =0.018), primarily driven by an increased baseline flow in non‐IRA (rest mean transit time 0.58 [0.32–0.83] versus 0.65 s [0.39–1.20], P =0.045), whereas the hyperemic flow was similar (hyperemic mean transit time 0.26 [0.20–0.42] versus 0.26 s [0.18–0.35], P =0.873). No differences were found regarding index of microcirculatory resistance (15.6 [10.4–21.8] in non‐IRA versus 16.7 [11.6–23.6] U in SA vessels, P =0.559). During adenosine infusion, the hyperemic response was similar in both groups (non‐IRA versus SA vessels) in terms of the resistive reserve ratio (3.1±2.1 versus 3.7±2.2, P =0.118). Conclusions: In the subacute phase of myocardial infarction, non‐IRA show an increased baseline flow that may cause abnormal coronary flow reserve despite preserved hyperemic flow. In non‐IRA, microcirculatory resistance and adenosine‐induced hyperemic response are similar to those found in SA patients. From a physiological perspective, these findings support the use of fractional flow reserve to interrogate non‐IRA during the subacute phase of myocardial infarction. Abstract : See Editorial Koh and Samady